Computerised building cost estimating system - Marjuki, Mofti (2006)
Estimating is an important process in order to prepare cost estimating for a proposed project. Cost estimate will give client an overview towards the total cost needed to be spent based on design. Due to the importance of the cost estimate for a proposed project, the utilization of computer to prepare cost estimate should therefore be practiced. The entry of computer technology in the estimating practice is a major event in the improvement of the traditional estimating method by reducing estimate preparation time, reducing the amount of paperwork required for the conventional data storage, and improving the quality of documentation. However, the actual use of the computer varies. Some companies use the computer for all projects and others do not use at all. The software are under-utilized due to its inefficiency in terms of difficulty, cost and because the program does not match with the company’s style of estimate This study is intended to identify estimating techniques used by contractors for cost estimate, to identify problem causes using that techniques and to develop a computerized cost estimating system for contractors. The study has found out that most of the contractors were using approximate quantity estimating technique for their cost estimations using computers. However, some of them still prefer to use manual technique as it is easier to apply. Microsoft Excel is the popular software used by contractors to prepare estimate. However, there are disadvantages in using Microsoft Excel is that users have to create suitable format for each estimating work. A computer-aided-project-cost-estimating system has been created to fulfill the needs mentioned. The result of this research was a cost estimating system application named as COES (Cost Estimating System) With the fulfill utilization Microsoft Access 2003 and other Microsoft Access functions, COES has been able to produce cost estimating automatically. This system serves as a systematic framework comprising elements of building works in order to help contractors to prepare a more precise and systematic cost estimate